Efektivitas Penggunaan Media Belajar Flashcard Aksara Jawa Terhadap Ketrampilan Menulis Aksara Jawa Legena Peserta Didik Madrasah Ibtidaiyah Kelas III - Wiranti, Dwiana Asih; Af’idatul Hasanah, Ummi Awwaliyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
The large number students of elementary or islamic elementary school who think that Javanese language material is material that is difficult to understand because of its diverse forms is the background for this research. This research aims to improve the ability and skills to write the Javanese Legenda script for class III students at MI Darul Huda 02 Karanggondang using the Javanese script Flashcard learning media. The research method that researchers use is descriptive quantitative research method. The research subjects were 27 class III students at MI Darul Huda 02 Karanggondnag. The research instruments used by researchers included 2 tests, namely Pre-Test and Post-Test and analyzed student score data using SPSS 20.0. The research results prove that there is a significant increase in value when conducting research. When the Pre-Test obtained an average score of 69.62, there were 16 students whose scores were above the KKM (Minimum Completeness Criteria), namely 70. Meanwhile, in the Post-Test, they obtained an average score of 91.29. According to the research results, it can be concluded that the Javanese script writing skills for Class III Islamic Elementary Scool Darul Huda 02 Karanggondang have increased by an average score of 21.67 from meeting 1 to meeting 4. It can be concluded that the use of Javanese script Flashcard learning media is very effective in improving the Javanese script writing skills of Madrasah Ibtidaiyah students or other equivalent education.